Semantic and Science Qur’anic Studies: Relationship Genetic Inheritance and Parental Education Model for Children in Qissah Ibrahim - Noor, Sabiq; Faruq, Abdul Qudus Al; Yardho, Moh.; Chatun, Chumaira; Hilmi Faiz Al Azzam (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2025)
This article investigates the concept of genetic inheritance and parental education in the Qur’an by focusing on the story of Prophet Ibrahim, his two wives (Hajar and Sarah), and their sons, Ismail and Ishaq. Using a semantic approach, it analyzes the terms ghulam, halim, and alim as found in Surah As-Saffat (101) and Adh-Dhariyat (28), applying two linguistic theories—derivation (isytiqaq) and correlation (munasabah) in combination with a scientific framework. The aim is to explore how these Qur’anic expressions contribute to understanding the interplay between inherited traits and educational influence in shaping character. Modern genetics emphasizes the biological transmission of traits, while developmental psychology highlights the importance of environment and parenting. The Qur’an appears to acknowledge both, suggesting that children's characteristics are shaped not only through lineage but also through nurturing. This is illustrated in the distinct personalities of the sons of Hajar and Sarah, which are examined through linguistic and contextual analysis. Findings reveal that ghulam refers to a child nearing adulthood, alim denotes deep and inherent knowledge, and halim describes patience and emotional restraint. These attributes reflect both inherited and cultivated virtues present in the characters of Ibrahim's sons. While the article does not establish a definitive